Isolation and Potency Test of Endophytic Bacteria as Nitrogen Fixer from Mangrove Plant in Lamongan - Fatimah, Fatimah; Izzatul Millah, Annida; Lailatul Ayu Fadilah, Risky; Salsabila, Syarifah; Asrifah Ramly , Zakia; Sugiarti , Tipuk; Nurhariyati , Tri; Affandi , Moch (Universitas Negeri Surabaya, 2022)
Endophytic bacteria are microorganisms that live in plant tissues and some of them contribute to nitrogen fixation for plants. This study aimed to isolate and identify endophytic bacteria from mangroves of Kutang Beach, Lamongan, which potentially as nitrogen fixing bacteria. Bacterial Isolates were used as candidates for biofertilizers. Leaves samples were taken from 10 sampling points. Bacterial isolation was initiated by sterilizing the surface of the leaves sample and grinding it aseptically. Isolation was carried out with a pour plate method on Nutrient Agar medium. Screening for endophytic bacteria's potential as N-fixing agent was carried out by growing the bacterial isolates on a semi-solid Nitrogen Free Bromothymol Blue (NFB) medium. The isolates that produced a positive reaction with a change in the color of the medium to blue were then subjected to macroscopic (shape, color, elevation, and the edge of the colony) and microscopic observations (Gram stain and bacterial cell measurements). The isolates showed the fastest change in the color of the medium were identified by the molecular marker of the 16S rRNA gene. The data obtained were analyzed descriptively. As many as 20 isolates were obtained from the mangroves of Kutang Lamongan Beach, and ten isolates of twenty potentially as nitrogen-fixing bacteria. The ten nitrogen-fixing bacteria isolates had varying macroscopic characteristics. The microscopic characteristics showed that eight isolates had Gram-positive bacilli, and two isolates were Gram-negative with varying bacterial sizes. Based on the 16S rRNA gene sequence, the most potential of nitrogen-fixing bacteria was LMG II-14 isolate and identified as Paenibacillus alvei LMG II-14 with 99.36% similarity to Paenibacillus alvei strain DSM 29 based on the NCBI database. The ten nitrogen fixing isolates that have been obtained can later be used as candidates for biofertilizer composition, especially Paenibacillus alvei LMG II-14.